COMPARISON BETWEEN CHICKEN AND RED MEAT SHAWARMA FOOD FOR BACTERIAL CONTAMINATION - SAEED, WAZIRA Q.; MOHAMMAD, ISSA M. (Journal of Duhok University, 2021)
The present study was conducted on 100 samples of two types of Shawarma fast-food (chickens meat Shawarma and red meat Shawarma) in restaurants and Cafeterias of Soran city, Kurdistan region, Iraq; for four months during 2021. The aim of this investigation was to compare both types of Shawarma for bacterial contamination. The collected samples were transferred to the laboratory using cold box and analyzed within two hours. The samples were prepared for bacteriological analysis via observed and total viable count (TVC) of bacteria; Total coliform count, Staphylococcus bacteria count, Detecting of Salmonella and Examining culture (for identification and isolating Grams Stain bacteria). The main results were as follow; TVC bacteria percentages in chicken and red meat Shawarma were (82 vs. 94) %, respectively; with values of (9 104 vs. 14 104) cfu/g, respectively. The counterparts’ percentages of Coliform contamination were (10 vs. 14) %, respectively; with values of (27 102 vs. 2 103) cfu/g, respectively. Staphylococcus aureus, Staphylococcus epidermidis, Salmonella, Shigella spp and Pseudomonas bacteria recorded (18, 12, 20, 24 and 2) %, respectively for both types of Shawarma. The highest positive and significant (P<0.01) correlation coefficient was found between Staphylococcus aureus and Staphylococcus epidermidis count (0.762) in chicken’s Shawarma. This study discovered some dangerous types of Coliforms for the first time in Shawarma samples (Raoulttella ornithinolytica, Enterobacter hormaechei, and Aeromonas salmonicida).